IMPLEMENTATION OF INNOVATIVE BRIGADE-LABORATORY METHOD ON THE TERRITORY OF UKRAINE IN THE 20s OF XX CENTURY - Воробйова, Лоліта (Modern engineering and innovative technologies, 2023)
The article examines the active phase of the introduction of the adapted Dalton-Plan pedagogical technology in the form of a brigade-laboratory method on the territory of Ukraine during the innovative Ukrainian period (1917-1932)